2013
DOI: 10.1155/2013/852698
|View full text |Cite
|
Sign up to set email alerts
|

Stationary Patterns of a Cross-Diffusion Epidemic Model

Abstract: We investigate the complex dynamics of cross-diffusionSIepidemic model. We first give the conditions of the local and global stability of the nonnegative constant steady states, which indicates that the basic reproduction number determines whether there is an endemic outbreak or not. Furthermore, we prove the existence and nonexistence of the positive nonconstant steady states, which guarantees the existence of the stationary patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Cross-diffusion of the susceptible is also applied to the spatial epidemic model. This term represents the tendency of the susceptible to stay away from the infected since they are able to recognize the infected [4,5,12,24,37,41,43]. The results of this study indicate that susceptible cross-diffusion has an influence on the spread of an infectious disease and the pattern dynamics.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Cross-diffusion of the susceptible is also applied to the spatial epidemic model. This term represents the tendency of the susceptible to stay away from the infected since they are able to recognize the infected [4,5,12,24,37,41,43]. The results of this study indicate that susceptible cross-diffusion has an influence on the spread of an infectious disease and the pattern dynamics.…”
Section: Introductionmentioning
confidence: 93%
“…To prevent this to happen again, there must be a study on the behavior patterns of people moving who are still infected, from one place to another especially to areas with high density of the susceptible such as for work or study. As a result, this study addresses a spatial epidemic model, not only with cross-diffusion of the susceptible as in previous studies [4,5,12,24,37,43], but also with cross-diffusion of the infected to illustrate the abovementioned situation. The diffusion coefficient can be positive, zero or negative [16,37,40].…”
Section: Introductionmentioning
confidence: 95%
“…Many studies indicate that spatial epidemiology with selfdiffusion has become a principal scientific discipline aiming at understanding the causes and consequences of spatial heterogeneity in disease transmission [3]. In these studies, reaction-diffusion equations have been intensively used to describe spatiotemporal dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Turing's revolutionary idea was that the passive diffusion could interact with chemical reaction in such a way that even if the reaction by itself has no symmetrybreaking capabilities, diffusion can destabilize the symmetric solutions with the result that the system with diffusion has them [12]. In these studies [3,[13][14][15][16][17][18][19][20], via standard linear analysis, the authors obtained the conditions of Turing instability, and, via numerical simulation, they showed the pattern formation induced by self-diffusion or cross-diffusion and found that model dynamics exhibits a diffusion controlled formation growth to stripes, spots, and coexistence or chaos pattern replication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation